The potential of fungi in the bioremediation of pharmaceutically active compounds: a comprehensive review - Amobonye, Ayodeji; Aruwa, Christiana E.; Aransiola, Sesan; Omame, John; Alabi, Toyin D.; Lalung, Japareng (Frontiers in Microbiology, 2023)
The ability of fungal species to produce a wide range of enzymes and metabolites, which act synergistically, makes them valuable tools in bioremediation, especially in the removal of pharmaceutically active compounds (PhACs) from contaminated environments. PhACs are compounds that have been specifically designed to treat or alter animal physiological conditions and they include antibiotics, analgesics, hormones, and steroids. Their detrimental effects on all life forms have become a source of public outcry due their persistent nature and their uncontrolled discharge into various wastewater effluents, hospital effluents, and surface waters. Studies have however shown that fungi have the necessary metabolic machinery to degrade PhACs in complex environments, such as soil and water, in addition they can be utilized in bioreactor systems to remove PhACs. In this regard, this review highlights fungal species with immense potential in the biodegradation of PhACs, their enzymatic arsenal as well as the probable mechanism of biodegradation. The challenges encumbering the real-time application of this promising bioremediative approach are also highlighted, as well as the areas of improvement and future perspective. In all, this paper points researchers to the fact that fungal bioremediation is a promising strategy for addressing the growing issue of pharmaceutical contamination in the environment and can help to mitigate the negative impacts on ecosystems and human health.